Analysis of peristaltic nanofluid flow in a microchannel - Mokgwadi, Ronny Maushi (My University, 2022)
Nanofluids are a class of heat transfer fluids created by suspending nanoparticles in base fluids. Due to their enhanced thermal conductivity, nanofluids are fast replacing conventional heat transfer fluids like water, mineral oil, ethylene glycol and others. They contribute to advancement of technology and modernity through pertinent applications in fields such as biomedical, automotive industry, cooling technologies and many others. This study documents a survey of nanofluids and their applications and an investigation of peristaltic nanofluid flow through a two dimensional microchannel with and without slip effects. Peristaltic fluid transport plays an important role in engineering, technology, science and physiology. The Buongiorno model formulation is employed and the governing equations for peristaltic nanofluid flow in a two dimensional microchannel are non-dimensionalised and solved semi-analytically using the Adomian decomposition method. Series solutions for axial velocity, temperature and nanoparticle concentration profiles are coded into symbolic package MATHEMATICA for easy computation of the numerical solutions. The effects of the various parameters embedded in the model are simulated graphically and discussed quantitatively and qualitatively. The results are compared with those in literature that were obtained using other approximate analytical methods and the homotopy analysis method. The study revealed that the Brownian motion, thermophoresis, buoyance and the slip parameters have significant influence on the peristaltic flow axial velocity, temperature and nanoparticle concetration profiles. In the flow without slip, both the Brownian motion and thermophoresis parameters caused a cooling effect around the channel walls and a marginal temperature enhancement in the channel core region and significant flow reversal was noticed in the channel half-space with maximum axial velocity recording in the channel core region. In the slip flow, both Brownian motion and thermophorisis had a retardation effect on the nanoparticle concentration profile.
Thesis (M. Sc. (Applied Mathematics)) -- University of Limpopo, 2022
Keywords: Nanoparticles; Thermal conductivity; Mathematica (Computer program language); Brownian motion processes; Nanoparticles; Brownian motion processes; Nanofluids; Fluid mechanics